2013
DOI: 10.5402/2013/980824
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of Exercise Training in Hypertension

Abstract: Hypertension is a signi�cant health concern. Hypertension leads to compensatory pathologic hypertrophy and impaired cardiac function. Lifestyle modi�cations such as exercise are encouraged for hypertensive patients. Some studies have shown that exercise training can reverse pathological hypertrophy. Conversely, studies on animal models of hypertension have shown increased cardiac growth with exercise training. Despite the further induction of hypertrophy, exercise training seems protective against cell death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 117 publications
1
6
0
Order By: Relevance
“…Thus, it may be suggested that TS animals exhibited a prototype of physiological myocardial stimulus associated to preserved cavity geometry and improved cardiac function (Ellison et al, 2012). These benefits occurred regardless of a reduction in gradient pressure, which supports the hypothesis that the exercise can attenuate myocardial remodeling independent of the cardiac overload lowering the effects of exercise (Libonati, 2013). Overall, benefits from the exercise may explain the improved functional capacity in trained animals, as noted for the increase in VO 2 max—a gold standard to assess exercise tolerance (Carlson, 1955).…”
Section: Discussionsupporting
confidence: 73%
“…Thus, it may be suggested that TS animals exhibited a prototype of physiological myocardial stimulus associated to preserved cavity geometry and improved cardiac function (Ellison et al, 2012). These benefits occurred regardless of a reduction in gradient pressure, which supports the hypothesis that the exercise can attenuate myocardial remodeling independent of the cardiac overload lowering the effects of exercise (Libonati, 2013). Overall, benefits from the exercise may explain the improved functional capacity in trained animals, as noted for the increase in VO 2 max—a gold standard to assess exercise tolerance (Carlson, 1955).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, habitual physical activity, and chronic exercise, are likely ideal adjunct treatment strategies for cardiac dysfunction and associated mortality in renal disease. Indeed, exercise has already been shown to improve quality of life and reduce hospitalization in a number of other cardiovascular diseases (9,18,29,43). Consequentially, further clinical study is needed to confirm our findings and demonstrate the beneficial effects of exercise in patients with CKD.…”
mentioning
confidence: 56%
“…Specifically, coronary flow rate was preserved with wheel running, suggesting improved myocardial perfusion. In addition, cardiac hypertrophy was not further augmented in the AI-WR group, a finding that contrasts previous studies conducted in other models of CVD (29). LV NO may have conferred these effects because it is suggested to prevent cardiac hypertrophy and mediate coronary vasodilation via guanosine 3=,5=-cyclic monophosphate (cGMP)-dependent mechanisms (17).…”
mentioning
confidence: 59%
See 2 more Smart Citations